2018
DOI: 10.3390/ijerph15061187
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Physical Fitness and Exercise Self-Efficacy and Its Contribution to the Relationship between Body Dissatisfaction and Physical Fitness in Female Minority Children

Abstract: Body Dissatisfaction (BD) and low physical self-concept and exercise efficacy have been linked to poor physical fitness levels and adverse health outcomes in children. The purpose of this study was to examine the relationship between BD, physical fitness, exercise self-efficacy, and self-Perception of Physical Fitness (PFP) in Latina and Black female children. Twenty-eight Latina and Black children enrolled in an elementary afterschool program, aged 8–12, completed surveys evaluating body dissatisfaction, exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
1
8
0
4
Order By: Relevance
“…Similar results noted that during adolescence there are differences that arise in motoric abilities and those are mostly expressed at the age of 13. Moreover, some studies stated that weaker motoric among females could not be prescribed only to morphological specifics, but also to the lower level of physical activity, and especially to the lower engagement in sport and recreational activities [53][54][55][56][57][58]. Studies underlined that, with increasing age, motoric abilities are improved, and the females reach the top in motoric abilities at age 14-15 [59][60][61].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results noted that during adolescence there are differences that arise in motoric abilities and those are mostly expressed at the age of 13. Moreover, some studies stated that weaker motoric among females could not be prescribed only to morphological specifics, but also to the lower level of physical activity, and especially to the lower engagement in sport and recreational activities [53][54][55][56][57][58]. Studies underlined that, with increasing age, motoric abilities are improved, and the females reach the top in motoric abilities at age 14-15 [59][60][61].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that perceived fitness is closely associated with mental wellbeing [47]. Furthermore, it is likely that increased self-perceived fitness goes along with increased self-efficacy to engage in exercise and sport activities [72]. As highlighted in the introduction, mental disorders are often paralleled by a mind-set that may interfere with the adoption and maintenance of a physically active lifestyle (e.g., feelings of exhaustion, hopelessness, resignation, social withdrawal) [73].…”
Section: Discussionmentioning
confidence: 99%
“…Agility has been defined as “a rapid whole-body movement with change of speed or direction in response to a stimulus” [7]. This quality is recognized as an important component of efficacy in various tactical duties, and particularly, as an important facet of effectiveness in team sports [8,9,10,11]. Indeed, for some team sports, such as basketball, soccer or handball, agility is recognized as one of the most important determinants of overall success [12,13,14].…”
Section: Introductionmentioning
confidence: 99%